THE EFFECT OF DICTOGLOSS TECHNIQUE AND MOTIVATION ON THE WRITING ACHIEVEMENT OF THE EIGHTH GRADE STUDENTS OF SMPN I SUKASADA - ., MADE SUCI SUANDARI; ., Dr.Ni Made Ratminingsih, MA; ., Dr. I Gede Budasi,M.Ed,Dip.App.Lin (Jurnal Pendidikan Bahasa Inggris Indonesia, 2013)
Abstract The study aimed at investigating the effect of Dictogloss Technique and Motivation on the writing Achievement of the Eighth Grade Students of SMPN 1 Sukasada. This experimental research applied the post test only control group design by using factorial 2 x 2 factorial designs. The instruments used in this study to gain the data were the writing test, and the motivation questionnaire. The obtained data were analyzed by using two way ANOVA and Tuckey test. The findings of the study were as follows : (1) the writing achievement of the students who were taught by using Dictogloss Technique is higher than the writing achievement of those students who were taught by using Conventional Technique, 2) there is an interactional effect between the teaching techniques applied and the students? motivation on the students? writing achievement 3) the writing achievement of high motivation students taught by using Dictogloss Technique is higher than the writing achievement of those students who were taught by using Conventional Technique, 4) there is a significant difference on the writing achievement of low motivation students who were taught by using Dictogloss Technique and the writing achievement of those who were taught by using Conventional Technique. Therefore, it could be concluded that, Dictogloss Technique is more effective than Conventional Technique for high and low motivation students in teaching writing. Kata Kunci : Dictogloss Technique, motivation, and writing achievement Abstract The study aimed at investigating the effect of Dictogloss Technique and Motivation on the writing Achievement of the EightH Grade Students of SMPN 1 Sukasada. This experimental research applied the posttest only control group design by using factorial 2 x 2 factorial designs. The instruments used in this study to gain the data were the writing test, and the motivation questionnaire. The obtained data were analyzed by using two way ANOVA and Tuckey test. The findings of the study were as follows : (1) the writing achievement of the students who were taught by using Dictogloss Technique is higher than the writing achievement of those students who were taught by using Conventional Technique, 2) there is an interactional effect between the teaching techniques applied and the students? motivation on the students? writing achievement 3) the writing achievement of high motivation students taught by using Dictogloss Technique is higher than the writing achievement of those students who were taught by using Conventional Technique, 4) there is a significant difference on the writing achievement of low motivation students who were taught by using Dictogloss Technique and the writing achievement of those who were taught by using Conventional Technique. Therefore, it could be concluded that, Dictogloss Technique is more effective than Conventional Technique for high and low motivation students in teaching writing. keyword : Dictogloss Technique, motivation, and writing achievement